Regulatory Effect of SlyA on rcsB Expression in Salmonella enterica Serovar Typhimurium - Ballesteros, María Florencia (2019)
The Salmonella enterica serovar Typhimurium RcsCDB system regulates the synthesis of colanic acid and the flagellum as well as the expression of virulence genes. We previously demonstrated that the rcsC11 mutant, which constitutively activates the RcsB regulator, attenuates Salmonella virulence in an animal model. This attenuated phenotype was also produced by deletion of the slyA gene. In this work, we investigated if this antagonistic behavior is produced by modulating the expression of both regulator-encoding genes. We demonstrated that SlyA overproduction negatively regulates rcsB transcription. A bioinformatics analysis enabled us to identify putative SlyA binding sites on both promoters, PrcsDB and PrcsB, which control rcsB transcriptional levels. We also determined that SlyA is able to recognize and bind to these predicted sites to modulate the activity of both rcsB promoters. According to these results, SlyA represses rcsB transcription by direct binding to specific sites located on the rcsB promoters, thus accounting for the attenuated/virulence antagonistic behaviors. Moreover, we showed that the opposite effect between both regulators also physiologically affects the Salmonella motility phenotype. In this sense, we observed that under SlyA overproduction, PrcsB is repressed, and consequently, bacterial motility is increased. On the basis of these results, we suggest that during infection, the different RcsB levels produced act as a switch between the virulent and attenuated forms of Salmonella. Thereby, we propose that higher concentrations of RcsB tilt the balance toward the attenuated form, while absence or low concentrations resulting from SlyA overproduction tilt the balance toward the virulent form.